ANALISIS KETIMPANGAN PEMBANGUNAN EKONOMI DAN KETIMPANGAN DISTRIBUSI PENDAPATAN DI PROVINSI KALIMANTAN SELATAN (STUDI KASUS KOTA BANJARMASIN DAN KABUPATEN TANAH BUMBU) - SUNTARI, MARTIN VEGARIKA; YUNANI, AHMAD (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study aims to find out how the level of economic development inequality and the inequality of income distribution in the city of Banjarmasin and Tanah Bumbu Regency and how comparative the economic development inequality and the inequality of income distribution in the two regions. This study uses secondary data from the time period 2013-2017 obtained from BPS. Analysis of the level of inequality of economic development by using the Williamson index, while to analyze the inequality of income distribution using the index gini ratio.               The comparative results of the Williamson index and the gini ratio index during 2013-2017 found that each analysis tool had different results so that it can be explained when the level of regional economic development inequality in the Tanah Bumbu Regency area with an average of 0.171 occurred due to the economy that relies on natural resources (mining and excavation), lack of smooth mobility of goods and services (distribution of goods and migration). However, the level of inequality in income distribution is low with an average of 0.312 because the depreciation of people's work is not much different so that the income distribution is more evenly distributed. When the inequality of economic development in the city of Banjarmasin is low with an average of 0.021, it occurs because the city of Banjarmasin is the center / concentration of the economy in the Province of South Kalimantan (the provincial capital) besides having a more complete infrastructure availability than other regions, an average of 0.354 occurs because of differences in the types of work and skills owned by the people of Banjarmasin City and has a small area so that there is an inequality in income distribution.Keywords: Williamson Index, and Gini Ratio Index.